Analysis of Basic Badminton Skills in Elementary School Students - Farrel, Aura; Mudjihartono, Mudjihartono; Hambali, Burhan; Hidayat, Yusuf; Yudiana, Yunyun (TEGAR: Journal of Teaching Physical Education in Elementary School, 2023)
This study aimed to analyze the basic badminton skills of elementary school students. The descriptive method was used in the study. This study involved 42 students (22 male students, 20 female students) of three elementary schools in Bandung City. Participants were selected using purposive sampling with the following inclusive criteria (1) aged 10-12 years and (2) following badminton extracurricular activities. The instrument used in this research was an instrument model for assessing badminton skills measuring two basic skills, namely high serve and clear lob skills. Obtained data were analyzed using descriptive statistics analysis and correlational test using SPSS software version 29.0. The results of the analysis showed that the student skills were divided into two categories, namely good and very good categories. Meanwhile, the correlational analysis showed that there was a correlation between high service and clear lob skills with a correlation coefficient of 0.62 and a p_value of 0.001. It indicates that the high service and clear lob basic skills have an impact on each other in game conditions and are interrelated in basic skills. Furthermore, based on the findings, the high service and clear lob basic skills in badminton of elementary school students taking part in badminton extracurricular were generally categorized as good and very good, since high service and clear lob skills are the skills that can be used as parameters of basic and primary skills to be mastered by students.